Effect of Methanolic Extract of Green Algal Enteromorpha Intestanalis on the Bioactivity of Giardia lamblia Parasite - Abdul Wahab Raisan Ayal (Institute of Medico-legal Publications Pvt Ltd, 2021)
The present study was conducted to detect the effect of Enteromorpha intestanalis methanol extract and study of its therapeutic effect in male Mus musculus experimentally infected with Giardia lamblia parasite, The mice infected with the parasite were dosed with the aforementioned extract at a concentration of (2, 2.5, 3) mg / ml at a dose rate per day for 25, 20, 15) days, and examining the faeces of the mice to monitor the change in the parasite preparation after the extract with the extract, and the results showed that the extract of the moss was Effective in reducing the numbers of encapsulated and feeding phases in mice infected with the parasite. The highest rate of killing of the feeding and encapsulated phases was recorded at a dose of (3) mg / ml during the twenty-five days’ period. Specific disclosures were made of chemicals for secondary metabolism of the algae extract, which indicated the presence of chemically effective compounds such as alkaloids, phenols, flavonoids, cyclosides, turpenoids, tannins, soaps and carotenoids. During the experiment, the therapeutic efficacy of the extract was calculated (64.30%). The chemical compounds of the algae extract were diagnosed using the Gas chromatography mass spectroscopy (Gc-mass) technique.